The Empowering Jumantik Cadres through Education as an Effort to Prevent Dengue Hemorrhagic Fever - Ernawati; Dameria Br Saragih; Siti Qorina Ramadhani; Bayu Tunggal Djimantoro; Ilna Safira Zahra (Sekolah Tinggi Ilmu Kesehatan RS Husada, 2026)
Dengue hemorrhagic fever (DHF) remains a major public health problem in Indonesia and requires active community participation in its prevention and control. This community service program aimed to empower larval monitoring cadres (Juru Pemantau Jentik [Jumantik]) by improving their knowledge of dengue, preventive measures, and mosquito larval inspection in residential settings in Sunter Agung Urban Village, Tanjung Priok Subdistrict, North Jakarta. The program consisted of educational sessions on dengue and its prevention, demonstrations of mosquito larval inspection techniques, and knowledge assessments using pre- and post-tests. A total of 21 Jumantik cadres participated in the program. Before the intervention, 47.6% of the participants had moderate knowledge, 28.6% had poor knowledge, and 23.8% had good knowledge. After the intervention, the post-test knowledge score increased to 71.4%. The Wilcoxon signed-rank test showed a statistically significant difference in knowledge scores before and after the intervention (Z = ?3.900, p < .001). These findings indicate that health education combined with demonstrations of mosquito larval inspection techniques was effective in improving the cadres’ knowledge and strengthening their role in community-based dengue prevention. Continuous mentoring and regular larval monitoring are recommended to sustain the cadres’ participation in dengue prevention and control. Keywords: Dengue Hemorrhagic Fever; education; Jumantik cadres; mosquito larvae inspection.